Isolated tuberculous thyroiditis - Sarwar, SM; Rahman, Masroor (Bangladesh Journal of Otorhinolaryngology, 2020)
Tuberculosis is a widespread infectious disease caused by various strains of Mycobacteria, usually Mycobacterium tuberculosis1.Tuberculosis generally affects the lungs ,but can also affect other parts of the body. Tuberculosis of the thyroid gland is an extremely rare condition. We report a case of a 35 years old female patient with isolated Tuberculous Thyroiditis presented as diffuse tenderness and pain in lower part of anterior neck with no visible neck swelling. Fine needle aspiration cytology (FNAC) from the thyroid gland revealed caseatingepitheloid granulomas consistent with tuberculosis. Bangladesh J Otorhinolaryngol; April 2016; 22(1): 62-64